Climate anxiety as posthuman knowledge - Candice Boyd; Hester Parr; Christopher Philo (Wellbeing, Space and Society, 2023)
The American Psychological Association defines ‘climate anxiety’ or ‘eco-anxiety’ as a chronic fear of environmental doom (Clayton et al., 2017, p.68 [Glossary]). This paper instead theorises climate anxiety as an emergent form of posthuman knowledge, albeit one that is dominated by vulnerability rather than affirmation. Put this way, the cultivation of ethical relationality through meaningful multi-species encounters holds potential for transforming this vulnerability and alleviating the anxiety. Offering both a reappraisal of early earth-writing by humanistic geographers and an engagement with recent work on ‘earth emotions’, including notions of ‘ecological grief’ and ‘mourning’, the article critically reviews lines of thinking – together constituting a new form of posthuman wellbeing studies – that challenge clinical understandings of climate anxiety by reimagining the purpose and mode of psychological intervention for the futures of earthly wellbeing.